The influence of rainbow scrapbook learning media on student learning motivation - Yanti, Fitri; Saragih, Fathul Amira; Subrata, Doni (CAHAYA PENDIDIKAN, 2023)
The low motivation of students in learning is partly due to the use of learning media which is still limited. The purpose of this study was to determine the effect of Rainbow Scrapbook media on the learning motivation of class IX students in the Integrated Social Sciences subject at SMP Negeri 50 Batam. This type of research is quantitative research with a quasi-experimental approach. The sampling technique used purposive sampling. The selected experimental class IX F consisted of 39 students and the control class IX D consisted of 40 students. The experimental class was given the treatment using Rainbow Scrapbook media, while the control class was given the treatment using textbook media. The research instrument is in the form of a learning motivation questionnaire with a Likert scale of 37 question items. The results of the research class based on the tabulation of the frequency distribution of 39 students obtained an average (mean) of 68.82, and the control class from the tabulation of the frequency distribution of 40 students obtained an average (mean) of 67.87. The t-test analysis obtained a t count of 1.664 and a t table of 1.660 with a significance of 0.05. Because the t count is greater than the t table, then Ha can be accepted and Ho is rejected, meaning that there is a significant effect of using Rainbow Scrapbook media on student learning motivation.